Intimate Visualities: Intimacy as Social Critique and Radical Possibility in Kyle Abraham and Carrie Schneider's Dance Response Project's I am Sold and Blood on the Leaves - Batiste, Stephanie Leigh (The International Journal of Screendance, 2018)
Choreographer and dancer Kyle Abraham and photographer and filmmaker Carrie Schneider position intimacy in screen dance as an affective hailing to viewers. The intimate visualities they achieve serve as an opportunity to critically hypothesize ways of being in community and understanding black visual relationships to subjectivity. In both explorations of meaning a production of close relationships to others, to notions of selfhood, and to blackness animate a radical love of others and of self. Their collaborations, the Dance Response Project, subtly, but powerfully tap persistent modes of black being and of theorizing the social new to creative discourse.